THE EFFECT OF AL(OH)4- ON THE DISSOLUTION RATE OF QUARTZ - Bickmore B.R.; Nagy K.L.; Gray A.K.; Brinkerhoff A.R. (My University, 2006)
The influence of Al(OH)4- on the dissolution rate of quartz at pH 10-13 and 59-89 °C was determined using batch experiments. Al(OH)4- at concentrations below gibbsite solubility depressed the dissolution rate by as much as 85%, and this effect was greater at lower pH and higher Al(OH)4- concentration. Dissolution rates increased with increasing temperature; however, the percent decrease in rate due to the presence of Al(OH)4- was invariant with temperature for a given H+ activity and Al(OH)4- concentration. These data, along with what is known about Al-Si interactions at high pH, are consistent with Al(OH)4- and Na+ co-adsorbing on silanol sites and passivating the surrounding quartz surface. The observed pH dependence, and lack of temperature dependence, of inferred Al(OH)4- sorption also supports the assumption that the acid-base behavior of the surface silanol groups has only a small temperature dependence in this range. A Langmuir-type adsorption model was used to express the degree of rate depression for a given in situ pH and Al(OH)4- concentration. Incorporation of the rate data in the absence of aluminate into models that assume a first-order dependence of the rate on the fraction of deprotonated silanol sites was unsuccessful. However, the data are consistent with the hypothesis proposed in the literature that two dissolution mechanisms may be operative in alkaline solutions: nucleophilic attack of water on siloxane bonds catalyzed by the presence of a deprotonated silanol group and OH- attack catalyzed by the presence of a neutral silanol group. The data support the dominance of the second mechanism at higher pH and temperature. ? 2005 Elsevier Inc. All rights reserved.
Keywords: DISSOLUTION; QUARTZ